AUDIT AND ANALYSIS OF ENERGY CONSUMPTION OF OFFICIAL BUILDING IN ITERA CAMPUS - Amna Citra Farhani; Didik Supriyadi (Journal of Science and Applicative Technology, 2018)
Decreasing of energy consumption for buildings has become a common issue in many countries. This makes rising in the importance of having an effort to conserve the energy use for consumption. Audit energy is a starting point to have the conservation energy effort. With audit energy, the energy consumption pattern of a system could be achieved and the scheme for decreasing energy consumption could be drawn. Higher education institution should be the agent to implement the energy conservation in society. This paper is aim to have energy audit and energy consumption pattern in ITERA. With the result, a scheme for energy consumption in ITERA will be presented. This scheme later will have impact on ITERA’s budget. In order to have this scheme, electrical energy consumption in every building in ITERA will be surveyed. Beside electrical energy, temperature and relative humidity in every room building will be measured. Secondary data as in building area and room schedule will be collected. This data will be analyzed and the expected data, that is the scheme for energy consumption decreasing will be recommended.